Corporate Manslaughter and Regulatory Reform - Almond, P. author. aut Link
XVIII, 224 p.
Keywords: This book provides an account of the international emergence of corporate manslaughter offences to criminalise deaths in the workplace during the last twenty years, identifying the limitations of health and safety regulation that have prompted this development.